2012
DOI: 10.1016/j.ygyno.2011.12.292
|View full text |Cite
|
Sign up to set email alerts
|

Impact of surgeon volume on patient safety in laparoscopic gynecologic surgery

Abstract: OBJECTIVE-To determine the impact of surgeon volume on patient outcomes in gynecologic laparoscopic surgery. METHODS-We reviewed all patients who underwent a laparoscopic procedure between January 2000 and December 2008. Surgeons were divided into 3 groups based on surgical volume. The mean number of surgeries per year was calculated for each surgeon. Means were categorized into 3 groups. The low-, medium-, and high-volume surgeon groups were compared with respect to level of surgical complexity and intraopera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…This likely reflects that our risk adjustment did not completely correct for the complexity of the patient/procedure that HVS undertake. 18 Gastrostomy and tracheostomy rates in this study were 23.1% and 13.2%, respectively. This is reasonable given that the published perioperative rates of these procedures are estimated at 4% to 14% for gastrostomy and 1% to 7% for tracheostomy, and these published numbers do not take into account the effects of adjuvant therapy.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…This likely reflects that our risk adjustment did not completely correct for the complexity of the patient/procedure that HVS undertake. 18 Gastrostomy and tracheostomy rates in this study were 23.1% and 13.2%, respectively. This is reasonable given that the published perioperative rates of these procedures are estimated at 4% to 14% for gastrostomy and 1% to 7% for tracheostomy, and these published numbers do not take into account the effects of adjuvant therapy.…”
Section: Discussionmentioning
confidence: 49%
“…After risk adjustment, HVS were independently associated with a complicated postoperative course. This likely reflects that our risk adjustment did not completely correct for the complexity of the patient/procedure that HVS undertake 18 …”
Section: Discussionmentioning
confidence: 98%
“…Concentrating these kinds of care at fewer sites could reduce costs of care and improve quality (Sternberg and Dougherty, 2015). Recent studies have indicated that a low volume of care in a particular area, for even routine surgeries, is associated with poor outcomes (Ley, 2014;Sternberg and Dougherty, 2015;Worley et al, 2012). Centralization efforts around care quality could both reduce system-level inefficiencies and increase alignment of the triple mission (patient care, education, and research).…”
Section: Coordination Among the Academic Medical Centers Can Prevent mentioning
confidence: 99%